2019
DOI: 10.3390/v11100890
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Purification, Chemical Synthesis, and In Vitro/In Vivo Evaluation of a Resveratrol Dimer, Viniferin, as an HCV Replication Inhibitor

Abstract: Oligostilbenoid compounds, a group of resveratrol multimers, display several anti-microbial activities through the neutralization of cytotoxic oxidants, and by inhibiting essential host and viral enzymes. In our previous study, we identified a series of oligostilbenoid compounds as potent hepatitis C virus (HCV) replication inhibitors. In particular, vitisin B, a resveratrol tetramer, exhibited the most dramatic anti-HCV activity (EC50 = 6 nM and CC50 > 10 μM) via the disruption of the viral helicase NS3 (IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…In 2019, the same authors confirmed the inhibitory capability of (þ)-e-viniferin against HCV [58]. The pure enantiomer (þ)-e-viniferin ((þ)-e-VF) ( Fig.…”
Section: Hepatitis C Virusmentioning
confidence: 72%
See 2 more Smart Citations
“…In 2019, the same authors confirmed the inhibitory capability of (þ)-e-viniferin against HCV [58]. The pure enantiomer (þ)-e-viniferin ((þ)-e-VF) ( Fig.…”
Section: Hepatitis C Virusmentioning
confidence: 72%
“…Eventually, in in vivo pharmacokinetic studies, after intraperitoneal injection in rats, vitisin B showed a preferred tissue distribution in the liver, which is a major organ of HCV replication [57]. Because of the difficulties to obtain the pure compound in substantial amounts for further investigation, studies on infected mice were not included [58].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…rotavirus (B. Yu et al, 2018), Human Immunodeficiency Virus (HIV) (Pflieger et al, 2013); hepatitis C virus (HCV) (Lee et al, 2019).…”
Section: Anti-tussive Molecules Like D-viniferin and Myricitrinmentioning
confidence: 99%
“…Previous studies have also suggested that -Viniferin shows potent antiviral activity against a variety of viruses viz. rotavirus 19 , Human Immunodeficiency Virus (HIV) 20 ; hepatitis C virus (HCV) 21 .…”
Section: Inter-residue Contacts and The Structural Flexibility Is Locmentioning
confidence: 99%